Generating Operator of XXX or Gaudin Transfer Matrices Has Quasi-Exponential Kernel - Mukhin, E.; Tarasov, V.; Varchenko, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We show that the difference equation Df = 0 for an M-valued function f has a basis of solutions consisting of quasi-exponentials.